’They Do What Institutions Should Do’: Border Solidarity in the Light of an Institutional Crisis - Fortarezza, Francesca (PARTECIPAZIONE E CONFLITTO, 2023)
While asylum policies at the EU borders get stricter and stricter, civil solidarity initiatives towards people on the move keep spreading and growing around the continent. By looking at these dynamics through the lens of an institutional crisis, this paper describes and interprets the components, practices and attitudes of solidarity initiatives within a relational field whose boundaries are defined by the (in)actions of state institutions in matters concerning the protection and reception of asylum-seekers and refugees. For this purpose, I engaged in a relational ethnography in Trieste, at the Italian-Slovenian border, taking myself the role of a solidarity actor and using this positionality as an epistemological and methodological tool of analysis. In this way, the article overcomes reductionist and mutually-exclusive categorizations of solidarity and claims instead that initiatives in support of people on the move are contextual and relational. At the same time, and because of that, it also brings to the surface the deepest and common roots of these projects, which ultimately lie in the political dissatisfaction for and moral condemnation of the current asylum regime.